Software dynamic pricing by an optimization deterministic model with presence of piracy - Mesbah, Rashid (2015)
This project presents an optimization model for pricing a monopolistic software application with presence of piracy. The purpose is raising revenue produced by product’s sale with adjusting prices in a price skimming strategy and minimizing amount of piracy. The model is a multifunctional price skimming optimization with simplex method which accompanied by deterministic and stochastic methods for calculating time intervals of each segment. Linear functions are used to describing demand of each segment. In addition a linear piracy function is proposed to making piracy a dynamic parameter. The model has the ability to apply penetration pricing and controlling market share. Windows 7 is chosen for case study. Optimizing case of Windows 7 is resulted in 8.2 percentage increase in revenue, while value of net market share is virtually constant. Therefore the developed model demonstrates its competence in optimizing revenue by modifying prices with presence of piracy. Results show that to face with piracy, range of price skimming must decreased in a way that highest price need to be intensely decreased and also lowest one must be slightly decreased. By using this strategy lowest loss in revenue due to piracy can be recurred. Effects of an escalation in piracy on proposed optimization model are: increase in number of sale, demand, selling portion, market share but decrease in price, price difference between segments, and revenue. Time intervals between successive prices, which are obtained for Windows 7, is obtained by deterministic and stochastic technics which are shown to be nearly equal due to large number of customers